On some methodological aspects of the cost-benefit evaluation in health economics - Corugedo de las Cuevas, Indalecio (Papeles de Europa, 2012)
The recent literature on cost-benefit analysis in Health Economics normally follows the methodology accepted by the Environmental Economics rather than the classical Human Capital hypothesis adopted successfully by the Economics of Education. In this paper we try to argue what could be the main reasons for such an investigation line.